2022
DOI: 10.3389/fphar.2022.757398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome and Medical Cost of Originator and Generic Antihypertensive Drugs: A Population-Based Study in Yinzhou, China

Abstract: Background: The substitution of generic drugs can effectively alleviate the rapid growth of drug costs; however, the clinical effectiveness and medical costs of originator products and generics were barely studied in China.Objectives: To compare the effectiveness of antihypertensive drugs and hypertension-related medical costs between originator and generic initiators in Yinzhou, China.Methods: We conducted a population-based retrospective cohort study using the Chinese Electronic Health Records Research in Yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
3
2
1
Order By: Relevance
“…30 In other markets where physicians and hospitals have historically profited from the sale of medicines to patients paying out of pocket, such as the United States and China, physicians continue to express distrust of generic medicines (including for cardiovascular disease) despite large scale studies showing that clinical outcomes do not vary by branding status or price. [4][5][6][31][32][33][34] In contrast with dynamics in the Indian market reported over a decade ago by Singal and colleagues, 35 pharmacists in our study reported receiving bigger discounts from manufacturers of premium products, potentially allowing them to reap significant margins by selling these products. While the hospital reported negotiating large discounts on branded products, high prices paid by uninsured patients for branded study medicines suggest that discounts are not passed on to consumers.…”
Section: Discussioncontrasting
confidence: 82%
“…30 In other markets where physicians and hospitals have historically profited from the sale of medicines to patients paying out of pocket, such as the United States and China, physicians continue to express distrust of generic medicines (including for cardiovascular disease) despite large scale studies showing that clinical outcomes do not vary by branding status or price. [4][5][6][31][32][33][34] In contrast with dynamics in the Indian market reported over a decade ago by Singal and colleagues, 35 pharmacists in our study reported receiving bigger discounts from manufacturers of premium products, potentially allowing them to reap significant margins by selling these products. While the hospital reported negotiating large discounts on branded products, high prices paid by uninsured patients for branded study medicines suggest that discounts are not passed on to consumers.…”
Section: Discussioncontrasting
confidence: 82%
“…34 In other markets where physicians and hospitals have historically profited from the sale of medicines to patients paying out of pocket, such as the United States and China, physicians continue to express distrust of generic medicines (including for cardiovascular disease) despite large-scale studies showing that clinical outcomes do not vary by branding status or price. [4][5][6][35][36][37][38] In contrast with dynamics in the Indian market reported over a decade ago by Singal et al, 39 pharmacists in our study reported receiving bigger discounts from manufacturers of premium products, potentially allowing them to reap significant margins by selling these products. Although the hospital reported negotiating large discounts on branded products, high prices paid by uninsured patients for branded study medicines suggest that discounts are not passed on to consumers.…”
Section: Discussioncontrasting
confidence: 98%
“…34 In other markets where physicians and hospitals have historically profited from the sale of medicines to patients paying out of pocket, such as the United States and China, physicians continue to express distrust of generic medicines (including for cardiovascular disease) despite large-scale studies showing that clinical outcomes do not vary by branding status or price. 4 6 , 35 38 …”
Section: Discussionmentioning
confidence: 99%
“…The results either showed no difference in the mean reduction in systolic BP, hypertension control rate, or CV outcomes 52 or demonstrated higher hospitalization rates for CVD in patients started with some of the branded drugs analyzed, possibly pointing to a difference in medication adherence in the brand prescription groups. 53 Indeed, in both studies the use of generic drugs unsurprisingly translated into lower medication costs.…”
Section: Generic Versus Branded Drugsmentioning
confidence: 99%